2011
DOI: 10.1152/ajprenal.00740.2010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of serum 1,25(OH)2Vitamin D3levels by fibroblast growth factor 23 is mediated by FGF receptors 3 and 4

Abstract: Fibroblast growth factor 23 (FGF23) is a phosphaturic hormone implicated in the pathogenesis of several hypophosphatemic disorders. FGF23 causes hypophosphatemia by decreasing the expression of sodium phosphate cotransporters (NaPi-2a and NaPi-2c) and decreasing serum 1,25(OH)2Vitamin D3 levels. We previously showed that FGFR1 is the predominant receptor for the hypophosphatemic actions of FGF23 by decreasing renal NaPi-2a and 2c expression while the receptors regulating 1,25(OH)2Vitamin D3 levels remained elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 52 publications
(75 reference statements)
0
67
0
Order By: Relevance
“…The FGFR pathway is involved in normal phosphate and vitamin D homeostasis, and preclinical development of FGFR inhibitors has been complicated by hyperphosphatemia-mediated tissue calcification, owing to blockade of FGF23 release from bone and of the FGF23 signal in kidney (47). FGF23 binds FGFR4 and the IIIc isoforms of FGFR1 and FGFR3 (2,48), but uncertainty remains about the relative contribution of individual FGFR subtypes to hyperphosphatemia (49)(50)(51)(52). In preclinical models, FGFR inhibition results in dynamic modulation of circulating FGF23 levels, with suppressed levels observed during periods of drug exposure (attributable to direct inhibition of FGF23 release from bone) and elevated levels upon drug withdrawal (driven by increased plasma phosphate and vitamin D levels acting on bone to stimulate FGF23 production; ref.…”
Section: Small-molecule Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…The FGFR pathway is involved in normal phosphate and vitamin D homeostasis, and preclinical development of FGFR inhibitors has been complicated by hyperphosphatemia-mediated tissue calcification, owing to blockade of FGF23 release from bone and of the FGF23 signal in kidney (47). FGF23 binds FGFR4 and the IIIc isoforms of FGFR1 and FGFR3 (2,48), but uncertainty remains about the relative contribution of individual FGFR subtypes to hyperphosphatemia (49)(50)(51)(52). In preclinical models, FGFR inhibition results in dynamic modulation of circulating FGF23 levels, with suppressed levels observed during periods of drug exposure (attributable to direct inhibition of FGF23 release from bone) and elevated levels upon drug withdrawal (driven by increased plasma phosphate and vitamin D levels acting on bone to stimulate FGF23 production; ref.…”
Section: Small-molecule Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Krejci . Further studies revealed that Fgfr3/Fgfr4 double-null mice have lower serum phosphorus levels and elevated FGF23 and 1,25(OH) 2-vitamin D 3 levels compared with WT mice (Gattineni et al 2011). The supraphysiological levels FGF23 and 1,25(OH) 2-vitamin D 3 may be responsible for the growth retardation of Fgfr3/Fgfr4 double-null mice (Larsson et al 2004, Kawai et al 2013, Bach et al 2014.…”
Section: Introduction On Growth Plate Developmentmentioning
confidence: 99%
“…19,20 FGF23 reduces the 1,25-dihydroxyvitamin level by inhibiting the renal 1-a-hydroxylase expression and promoting the 24-hydroxylase expression, thereby downregulating the amount of phosphate absorption from the gut and resorption from the bone. 21,22 Mutual regulation of FGF23 and parathyroid hormone has been reported in rodent models 23,24 and identified in clinical cases of hypophosphatemic rickets and chronic kidney disease. 25 In addition to these systemic and hormonal patterns of regulation, the FGF23 expression appears to be regulated locally by FGF23-producing cells and osteocytes through molecules such as dentin matrix protein-1 (DMP1) 26,27 and the phosphate-regulating gene with homology to endopeptidases on X chromosome (PHEX), 28 both of which are highly expressed in osteocytes.…”
Section: Introductionmentioning
confidence: 99%